Database Machine Drawings - Max-Planck-Gesellschaft zur Förderung der Wissenschaften (2008)
[Dt.:] Die Bilddatenbank Database Machine Drawings DMD ist Teil des Forschungsprojektes "The Relation of Practical Experience and Conceptual Structures in the Emergence of Science: Mental Models in the History of Mechanics", das vom Max Planck Institut für Wissenschaftsgeschichte (MPIWG) in Berlin gefördert wird. Die Datenbank bietet Zugang zu digitalisierten Maschinenzeichnungen aus der Zeit von ca. 1200-1650, welche komfortabel über unterschiedliche Sucheinstiege recherchiert werden können. Die Abbildungen sind vergrößerbar und werden mit Bildlegenden und Katalogisaten präsentiert. - [Engl.:] The database DMD is part of the research project The Relation of Practical Experience and Conceptual Structures in the Emergence of Science: Mental Models in the History of Mechanics, a project pursued by Department I of the Max Planck Institute for the History of Science (MPIWG), Berlin, headed by Jürgen Renn. In its context, a large number of original sources concerning the history of mechanics have been made available on the Internet as a digital research library, the Archimedes Project. In this broader context the database DMD is especially devoted to studying the practical knowledge of early modern engineers.